RESPONSE OF RAJMASH GENOTYPES TO FERTILIZER LEVELS IN KARNATAKA DURING RABI - GANAJAXI, -; HALIKATTI, S.I.; CHITTAPUR, B.M.; KAMANNAVAR, P.Y. (Annals of Agricultural Research, 2014)
The experiment was conducted at Main Agricultural Research Station, Dharwad during rabi season of 2004 under rainfed condition. The treatments comprised of 4 genotypes (Vaghya, Contender, HPR-35 and Arka Komal) and 3 levels of fertilizer (50%, 100% and 150% of RDF). Recommended dose of fertilizer for French bean is 62.5:100:75 kg of N:P2O5:K2O/ha. The experiment was laid out in a randomized block design with three replications.Varieties HPR-35 and Contender can begrown for grain purpose with the recommended dose of fertilizer during rabi in northern transition zone of Karnataka.